The relationship between effectiveness of job training and job satisfaction among non-academic staff at UiTM Pahang branch, Jengka Campus / Nur Syahira Mustapha - Mustapha, Nur Syahira (Faculty of Business and Management, 2019)
The researcher had selected a topic entitled "The Relationship Between Effectiveness of Job Training and Job Satisfaction Among Non-Academic Staff at UiTM Pahang Branch, Jengka Campus". The purpose of this study is to measure the effectiveness of job training among non-academic staff and to investigate whether there is a relationship between effectiveness of job training and non-academic staffs job satisfaction at UiTM Pahang Branch, Jengka Campus. This research is descriptive and correlational in nature. This research is conducted among the non-academic staff in all departments in this organization. The total population of this study is about 140 of non academic staff and 103 (93.64%) took part in this investigation. This study is beneficial to employees and also organizations. The sampling frame includes the actual list of names and the total number of non-academic staff working at UiTM Pahang Branch, Jengka Campus. The sampling technique applied for this research is Convenience Random Sampling Technique. Based on the findings and results of analysis, the researcher can conclude that effectiveness of job training and job satisfaction have significant effect to the non academic staff.